Pemberian jahe instan terhadap kejadian mual muntah dan asupan energi pada ibu hamil trimester pertama - Nurfalah Setyawati; Mae Sri Hartati Wahyuningsih; Detty Siti Nurdiati (Jurnal Gizi Klinik Indonesia, 2014)
Background: Pregnancy causes increased energy metabolism, therefore needs of energy and other nutrients increase during pregnancy. Lack of energy and nutrients could adversely affect the mother and fetus. Nausea and vomiting is a common problem in the first trimester of pregnancy. If not treated the mother and fetus can be at risk of malnutrition due to lack of energy intake. Traditional treatment is an option that is considered safe. Ginger has been used to treat a variety of medical problems including nausea and vomiting. Ginger works in the digestive tract by increasing the gastric and intestinal motility.Objective: This study aimed to determine the effectiveness of instant ginger containing 290 mg ginger juice, to reduced the incidence of nausea and vomiting of pregnancy and increased maternal energy intake during the 24 hours.Method: The study design is experimental, the pre-post control group, involving 101 pregnant women with gestational age less than 15 weeks in RSB Sayang Ibu, puskesmas Klandasan Ilir and Sepinggan in Balikpapan. Research subjects were drawn at random and given the instant ginger or placebo, 2 times a day for a week. All of the subjects were assessed on the level of nausea, vomiting and a 24-hour energy intake during pre and post intervention. The use of drugs or supplementation from the doctor/midwife were recorded and not be stopped.Results: The rate of nausea and vomiting decreased significantly in the ginger group (52%) compared to placebo (17.7%) (p<0.05). Instant ginger may reduce nausea and vomiting rate 6 times higher than placebo (p<0.05). The average amount of energy intake (calories) for 24 hours increased significantly in the ginger group (1629.58 kcal ± 468.04 kcal; p<0.05) compared to placebo (1160.27 kcal ± 341.85 kcal; p>0.05). Instant ginger may increase the average amount of energy intake 24.5 times higher than placebo (p<0.05).Conclusion: Instant ginger effective to reduce nausea and vomiting of pregnancy and increase the amount of energy intake (calories) in pregnant women who experience nausea and vomiting of pregnancy.